Staging Organization Plays as critical commentaries on workplace life - Taylor, Steven S. (Palgrave Studies in Business, Arts and Humanities,, 2018)
This original and thought-provoking book takes a new approach to engaging with organizational theory and making sense of organizations. Consisting of seven plays written by the author, each is followed by a stimulating commentary by a noted scholar, exploring the wider contexts and values of applying theatre to organisational environments and management education. As the first work of this type in organisational theatre, this book will be of interest to scholars in the field of organisational learning, leadership training, art management, arts-based learning and creativity innovation. Alongside the scholarly discussion, the author provides the reader with the opportunity to experience the plays and apply them to education, research and the workplace. Including seven plays and commentaries Soft Targets- Capitalist Pigs- Blasphemy & Doubt- Cow Going Abstract- The Invisible Foot The Age of Loneliness- Through the Reading Glasses.